SO046REGULATION OF GUT MICROBIOTA AND HOST CO-METABOLISM BY POTASSIUM HOMEOSTASIS IN PATIENTS ON HEMODIALYSIS. (6th June 2020) - Raj, Dominic; Gao, Bei; Barrows, Elizabeth; Jagadeesan, Muralidharan; Amdur, Richard; Collins, Ashte; Regunathan-Shenk, Renu; Kincaid, Danielle; Omar, Badryah; Siddiqi, Muhammad
Abstract: Background and Aims: Gut microbiota composition is dysregulated in hemodialysis patients. However, the impact of potassium homeostasis on the gut microbiota and their metabolites has not been studied. Patiromer is a potassium binding polymer that exchanges calcium for potassium in the gastrointestinal (GI) tract, thereby increasing fecal potassium excretion and reducing serum potassium levels. Method: In this non-randomized, open label, 3-period crossover trial with repeated measures within each period, we investigated the effect of 12 weeks of treatment with patiromer on the microbiome profile and microbiota-related metabolites in 27 hemodialysis patients using multi-omics integration of data from shotgun metagenomic sequencing and untargeted and targeted metabolomic profiling. Data from hemodialysis patients at baseline was first compared with individuals without kidney disease (n=20). Results: We found that 18 bacterial species and 49 plasma chemical clusters were significantly different between patients and controls. Serum potassium decreased significantly from baseline (5.62±0.65 mEq/L) with patiromer treatment (4.80±0.46 meq/L) and increased during the post-treatment phase (5.45 ± 0.67 meq/L), (p<0.001). Three bacterial species and one bacterial pathway were altered by patiromer. We identified 52 serum metabolites, which were significantly different in patients at baseline compared with controls, and were partially reversed with patiromer treatment. Specifically, the serum levels of polyphenols such as vanillic acid, gallic acid and benzoic acid, and other microbiota-related metabolites such as 2, 6-diaminopimelic acid, 2-ketogluconic acid, indole-3-carboxaldehyde and 3-hydroxyphenylacetic acid were reduced by patiromer treatment. Conclusion: Our study suggests that control of hyperkalemia by patiromer alters the gut microbial composition and host co-metabolism in hemodialysis patients.